ANALYSIS OF THE FACTORS AFFECTING PUBLIC BEEF CONSUMPTION IN PANDAN SUB-DISTRICT, CENTRAL TAPANULI DISTRICT - Ismail Fauzi Siregar; Armyn Hakim Daulay; Tri Hesti Wahyuni; Ma'ruf Tafsin; Sayed Umar (Universitas Sumatera Utara, 2018)
Demands of animal foods from livestock (meat, eggs and milk) over time tends to increase in line with population growth, income, nutrition awareness, and improvement in education levels. But even though it has increased, the level of meat consumption of the Indonesian people is still categorized as very low. This study aims to determine the social and economic characteristics of households and analyze the factors that influence consumption of household beef in Pandan District. The analytical method used is descriptive analysis, namely by observing directly the social and economic conditions of the household, then using a questionnaire to obtain data on the socio-economic conditions of the household. The method of multiple linear regression analysis is used to analyze the factors that influence the consumption pattern of the household beef. The results of the study show that consumers of beef in Pandan Sub-district have different socio-economic characteristics, both in terms of education, age, number of family members and income. The socio-economic characteristics of beef consumers, namely education, age, number of family members and income significantly influence the amount of consumption simultaneously. Age, number of family members and income have a partial effect on the amount of beef consumption, while the education variable does not have a partial effect on the amount of beef consumption.